Allochthonous carbon is a major driver of the microbial food web – A mesocosm study simulating elevated terrestrial matter runoff. (August 2017) - Meunier, Cédric L.; Liess, Antonia; Andersson, Agneta; Brugel, Sonia; Paczkowska, Joanna; Rahman, Habib; Skoglund, Bjorn; Rowe, Owen F.
Abstract: Climate change predictions indicate that coastal and estuarine environments will receive increased terrestrial runoff via increased river discharge. This discharge transports allochthonous material, containing bioavailable nutrients and light attenuating matter. Since light and nutrients are important drivers of basal production, their relative and absolute availability have important consequences for the base of the aquatic food web, with potential ramifications for higher trophic levels. Here, we investigated the effects of shifts in terrestrial organic matter and light availability on basal producers and their grazers. In twelve Baltic Sea mesocosms, we simulated the effects of increased river runoff alone and in combination. We manipulated light (clear/shade) and carbon (added/not added) in a fully factorial design, with three replicates. We assessed microzooplankton grazing preferences in each treatment to assess whether increased terrestrial organic matter input would: (1) decrease the phytoplankton to bacterial biomass ratio, (2) shift microzooplankton diet from phytoplankton to bacteria, and (3) affect microzooplankton biomass. We found that carbon addition, but not reduced light levels per se resulted in lower phytoplankton to bacteria biomass ratios. Microzooplankton generally showed a strong feeding preference for phytoplankton over bacteria, but, in carbon-amended mesocosms which favored bacteria, microzooplankton shifted their diet towards bacteria. Furthermore, low total prey availability corresponded with low microzooplankton biomass and the highest bacteria/phytoplankton ratio. Overall our results suggest that in shallow coastal waters, modified with allochthonous matter from river discharge, light attenuation may be inconsequential for the basal producer balance, whereas increased allochthonous carbon, especially if readily bioavailable, favors bacteria over phytoplankton. We conclude that climate change induced shifts at the base of the food web may alter energy mobilization to and the biomass of microzooplankton grazers.